2020
DOI: 10.1055/s-0040-1713889
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban for Stroke Prevention in Atrial Fibrillation: Why are Event Rates Higher in Clinical Practice than in Randomized Trials?—A Systematic Review

Abstract: Background Recent reports suggest an important contribution from frequent off-label use of apixaban 2.5 mg twice daily to the higher rates of thromboembolic events observed in observational studies (OSs) relative to in randomized controlled trials (RCTs), and consequently, advocate against such use in all patients. Objectives To examine factors contributing to the higher thromboembolic event rates, we estimated the prevalence of off-label use in contemporary practice, and compared patient characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…An interesting analysis by de Vries et al showed why event rates are higher in clinical practice than randomized trials of stroke prevention in AF. 59 Also, Pandey et al published a systematic review and meta-analysis comparing lower versus standard international normalized ratio (INR) targets in AF, showing evidence that low INR targets may be associated with lower bleeding but has more adverse outcomes. 60,61 This work informed the 2021 APHRS guidelines on AF, and highlights the importance of standard targets and good quality anticoagulation control, with high TTR.…”
Section: Refining Anticoagulation Managementmentioning
confidence: 99%
“…An interesting analysis by de Vries et al showed why event rates are higher in clinical practice than randomized trials of stroke prevention in AF. 59 Also, Pandey et al published a systematic review and meta-analysis comparing lower versus standard international normalized ratio (INR) targets in AF, showing evidence that low INR targets may be associated with lower bleeding but has more adverse outcomes. 60,61 This work informed the 2021 APHRS guidelines on AF, and highlights the importance of standard targets and good quality anticoagulation control, with high TTR.…”
Section: Refining Anticoagulation Managementmentioning
confidence: 99%
“…This is understandable because a substantial number of patients treated in clinical practice have higher bleeding risks than those included in clinical trials. 9 10 Yet, many of the same patients are also at a higher risk of ischemic stroke, 9 10 and as a consequence, several authors have criticized the off-label use of the reduced dose. 8 11 12 13 14 …”
Section: Introductionmentioning
confidence: 99%
“…13,14 The data from randomized trials seem to be well augmented and supported by a wealth of real-world data despite the higher risk profiles of patients in observational nontrial cohorts. 15,16 When interpreting results of the open-label extension studies, we should realize that these patients were followed up regularly (e.g., 1, 6, and 12 months after entry into the openlabel extension of AVERROES, and every 6 months thereafter), Fig. 1 Risks of stroke/SE and major bleeding of patients who had been randomized to an NOAC during and after the end of double-blind phase, and those reported in the open-label extension period of RE-LY (RELY-ABLE) and AVERROES trials.…”
mentioning
confidence: 99%